Penerapan Realy Race terhadap Peningkatan Motivasi Belajar Bola Voli di SMPN 4 Kota Kediri - Mubarak, Jordan Agung; As-Safa, Ayyala Haqiqi Thoriq; Irfani, Muhammad Aditya; Kurniawan, Farel; Zalzabilla, Rahmadani Melia (Universitas Nusantara PGRI Kediri, 2024)
Education in Indonesia, particularly in junior high schools, is crucial for cultivating students' character and fundamental skills. Physical Education (PJOK) is integral to this process, utilizing various sports activities, including volleyball, to enhance physical, mental, and social abilities. However, many students exhibit low motivation in learning volleyball, often due to monotonous teaching methods. This study addresses this issue by applying the Reality Race method in volleyball education at SMPN 4 Kediri City. This innovative approach combines competition with engaging challenges, aiming to boost students' interest and participation in sports. Employing a Classroom Action Research (PTK) design, the study consists of two cycles involving planning, action, observation, and reflection. The findings indicate that the Reality Race method significantly enhances students' motivation, evidenced by rising motivation scores from the first to the second cycle. The effectiveness of this method not only fosters a more interactive and enjoyable learning environment but also improves fundamental volleyball skills, teamwork, and students' positive attitudes towards sports. Ultimately, this research advances the development of more dynamic and enjoyable PJOK teaching methods, contributing positively to students' engagement in physical education.